Psychological characteristics of developing geographical thinking in students - Narzullayev Nuriddin Homitovich (Goodwood Publishing, 2025)
Purpose: This study aims to examine the psychological characteristics that shape the development of geographical thinking among students, emphasizing the interplay between cognitive, emotional, and motivational factors. It seeks to identify effective psychological and pedagogical approaches that enhance analytical, creative, and environmental awareness through geography education. Methodology: The research employs a qualitative-descriptive approach supported by psychological and pedagogical analyses based on the theories of Vygotsky, Piaget, Bruner, Leontiev, Ausubel, and Gardner. Observations, diagnostic tests, surveys, interviews, and experimental teaching sessions were conducted to evaluate cognitive development, emotional engagement, motivation, and spatial reasoning across various age groups. Results: Findings reveal that geographical thinking develops most effectively in psychologically supportive and interactive learning environments. Emotional balance, intrinsic motivation, and individualized teaching approaches significantly enhance students’ spatial reasoning and problem-solving skills. The integration of visual aids, maps, and real-life examples strengthens long-term memory and analytical thinking. Furthermore, social interaction and collaborative learning stimulate critical and creative thought, transforming students into active participants in the learning process. Conclusion: The formation of geographical thinking is a multidimensional process rooted in cognitive, emotional, and motivational harmony. Teachers play a vital role by fostering motivation, empathy, and psychological comfort, enabling students to connect geographical concepts with real-world understanding and ethical awareness. Limitations: The study’s qualitative design limits statistical generalization and focuses primarily on school-based learning contexts. Contribution: This research contributes to educational psychology by integrating psychological principles into geography education, offering practical insights for teachers to enhance students’ intellectual, emotional, and environmental consciousness through active and meaningful learning.